Polygenic Contribution to Low-Density Lipoprotein Cholesterol Levels and Cardiovascular Risk in Monogenic Familial Hypercholesterolemia. (October 2020) - Trinder, Mark; Paquette, Martine; Cermakova, Lubomira; Ban, Matthew R.; Hegele, Robert A.; Baass, Alexis; Brunham, Liam R.
Abstract : Background: Familial hypercholesterolemia (FH) is a common autosomal codominant genetic disorder, which causes elevated levels of low-density lipoprotein cholesterol (LDL-C) and increased risk of premature atherosclerotic cardiovascular disease (ASCVD). Even among individuals with monogenic FH, there is substantial interindividual variability in LDL-C levels and risk of ASCVD. We assessed the influence of an LDL-C polygenic score on levels of LDL-C and risk of ASCVD for individuals with monogenic FH. Methods: We constructed a weighted LDL-C polygenic score, composed of 28 single-nucleotide variants, for individuals with monogenic FH from the British Columbia FH (n=262); Nutrition, Metabolism and Atherosclerosis Clinic (n=552); and UK Biobank cohorts (n=306). We assessed the association between LDL-C polygenic score with LDL-C levels and ASCVD risk using linear regression and Cox-proportional hazard models, respectively. ASCVD was defined as myocardial infarction, coronary or carotid revascularization, transient ischemic attack, or stroke. The results from individual cohorts were combined in fixed-effect meta-analyses. Results: Levels of LDL-C were significantly associated with LDL-C polygenic score in the Nutrition, Metabolism and Atherosclerosis Clinic cohort, UK Biobank cohort, and in the meta-analysis (β [95% CI]=0.13 [0.072–0.19] per a 20% increase in LDL-C polygenic score percentile, P <0.0001). Additionally, an elevated LDL-C polygenic score (≥80th percentile) was associated with a trend towards increased ASCVD risk in all 3 cohorts individually. This association was statistically significant in the meta-analysis (hazard ratio [95% CI]=1.48 [1.02–2.14], P =0.04). Conclusions: Polygenic contributions to LDL-C explain some of the heterogeneity in clinical presentation and ASCVD risk for individuals with FH. Abstract : Supplemental Digital Content is available in the text.